Assessment of the RegCM4-CORDEX-CORE performance in simulating cyclones affecting the western coast of South America - Crespo, Natália Machado; Reboita, Michelle Simões; Gozzo, Luiz Felippe [UNESP]; Jesus, Eduardo Marcos de; Torres-Alavez, José Abraham; Lagos-Zúñiga, Miguel Ángel; Torrez-Rodriguez, Limbert; Reale, Marco; Rocha, Rosmeri Porfírio da (Springer Nature, 2022)
In this study, we assess the performance of the Regional Climate Model version 4 (RegCM4) in simulating the climatology of the cyclones near the west coast of South America. The synoptic evolution and seasonality of these systems are thoroughly investigated. The analyses are based on four simulations from the CORDEX-CORE Southern America (SA) domain, at 0.25° of horizontal resolution: one driven by ERA-Interim and three driven by different GCMs. The reference dataset is represented by ERA5. Cyclones were detected by an objective scheme in the period 1995–2005 and classified in three different classes: (i) Coastal Lows (CLs) and cyclones affecting the coast (CAC) (ii) crossing and (iii) not crossing the Andes. In general, RegCM4 is able to reproduce the climatology of cyclones affecting the western coast of SA. In particular: (i) CLs are shown to be more frequent in austral summer although their frequency is underestimated by the simulations in this season; (ii) CAC not crossing the Andes represent 76% of all CAC and are more frequent in winter, with simulation underestimating their frequency by ~ 22% due to the differences in the simulated upper-level jets, which tend to get weaker (by ~ 5–10 m s− 1) northwards of 30°S; (iii) the frequency of CAC crossing the Andes tends to be overestimated mainly in winter, which is associated with the combination of the stronger upper-level jets and weaker SLP in the simulations, especially southwards of 40°S.
Keywords: Climatology; Coastal lows; Cyclones; Regional climate modeling; Western South America